The macintosh way - Kawasaki, Guy (Harper Perennial, 1990)
The Macintosh Way is a "take-no-prisoners guide to marketing warfare" says Jean Louis Gasse, founder and president of Be, Inc. Must reading for anyone in the high-tech industry, it is valuable, insightful guide to innovation management and marketing for any industry.